PENINGKATAN CITA RASA KOPI ROBUSTA TERDEKAFEINASI MELALUI FERMENTASI ULANG MENGGUNAKAN MUCILAGE TIRUAN - Februadi Bastian; Heppy Love Rida Sinaga; Adiansyah Syarifuddin; Amiruddin Hambali (AGROINTEK, 2024)
Some consumers prefer coffee's flavor but not caffeine's adverse effects. Therefore, a decaffeination method is used to reduce the amount of caffeine in coffee. However, decaffeination can decrease the flavor of the coffee. Accordingly, this study aimed to examine the influence of re-fermentation utilizing imitative mucilage from sweet potato and passion fruit pulp on the taste of decaffeinated coffee. The study's Robusta coffee green bean samples were treated: non- decaffeination and re-fermentation; non-decaffeination and re-fermententation; decaffeination and fermentation; and fermentation and decaffeination. Each sample was roasted and evaluated for flavor using the cupping test, and tests to green beans were also conducted for total acid, total dissolved solids, pH, phenolic, and volatile compounds. The results of this study indicate that decaffeination can reduce the taste of robusta coffee, as seen from the decreased cupping test results. However, decaffeinated coffee beans re-fermented with imitative mucilage exhibited increased cupping test values, total phenols, and volatile compounds. The decaffeination and further fermentation treatments decreased the total acid and dissolved solids. In contrast, the re-fermentation treatment impacted the increase in pH, total phenolic, and volatile compounds